Analysis of main historical aspects and the geological contextin the historical legend of the “doña Ana tunnel” as part of amethodological assessment of its veracity - Sanabria-Coto, Iván J.; Bonilla-Hidalgo, Maureen A (Revista Geográfica de América Central., 2025)
This work was based on a compilation of the main historical aspects associated with the legend of the “doña Ana tunnel”, located between Paraíso and Cartago, Costa Rica, followed by a geospatial reconstruction of the hypothetical layout proposed for the aforementioned tunnel, composed of a straight line of 5,896 km between two properties that belonged to Pilar Anacleta Arnesto de Mayorga (1809-1877), an important historical figure of legend and related to the arrival and capture of the illustrious Honduran general José Francisco Morazán Quesada (1842). The characterization of the geological context of the proposed layout made it possible to identify its main underground conditions and the minimum design-construction elements for this type of work. In conclusion, through the applied methodology, the existence of the aforementioned tunnel within the narrative is ruled out, based on the complexity: underground, logistics, design-construction and its possible associated costs, in addition to the lack of consistent evidence registration. about its construction.